2010
DOI: 10.2215/cjn.04290609
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Management in Patients with Renal Failure who Experience an Acute Coronary Syndrome

Abstract: Background and objectives: Prior reports have suggested that patients with impaired renal function receive less aggressive care after an acute coronary syndrome (ACS). The aim of this study was to determine whether this held true in a contemporary cohort, after thorough adjustment for cotreatments/comorbidities. Design, setting, participants, & measurements: Patients who were admitted for an ACS in eight participating hospitals were stratified into three groups according to estimated creatinine clearance (CrC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…(27) Evidence suggests this treatment disparity has attenuated,(28) so we examined data from the last year of our study (2008) and found that 71% of our patients with eGFR <60ml/min/1.73m 2 initiated statin therapy within the 90days following an MI, compared to 90% of patients with eGFR >90 ml/min/1.73m 2 . Thus, while relative statin treatment effects may not differ by level of renal function, poor outcome rates and treatment rates do differ by level of renal function, suggesting that attention could be usefully focused on increasing treatment rates among patients with pre-dialysis chronic kidney disease.…”
Section: Discussionmentioning
confidence: 92%
“…(27) Evidence suggests this treatment disparity has attenuated,(28) so we examined data from the last year of our study (2008) and found that 71% of our patients with eGFR <60ml/min/1.73m 2 initiated statin therapy within the 90days following an MI, compared to 90% of patients with eGFR >90 ml/min/1.73m 2 . Thus, while relative statin treatment effects may not differ by level of renal function, poor outcome rates and treatment rates do differ by level of renal function, suggesting that attention could be usefully focused on increasing treatment rates among patients with pre-dialysis chronic kidney disease.…”
Section: Discussionmentioning
confidence: 92%
“…This latter finding is quite surprising and in contrast with the therapeutic nihilism often reported in CKD patients. [11,12] However, it must be pointed out that despite the greater use of drugs, the therapeutic goals in the I-DEMAND population were, generally speaking, unsatisfactory and especially so in CKD patients. Taking the two renal components into consideration separately, i.e.…”
Section: Prevalence and Clinical Correlates Of Chronic Kidney Diseasementioning
confidence: 99%
“…Additionally, adherence to medication recommendations concerning secondary prevention of disease progression has been shown to be poor in patients with CKD. [16][17][18][19][20] Again, data for long-term medication adherence according to recent guideline recommendations are lacking. In this study, we investigated the stage-specific impact of CKD on the outcome of patients with PAD, including a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%